The Emerging Role of the Inflammasome in Kidney Diseases - Chang, Anthony (2014)
PURPOSE OF REVIEW: This review focuses on the latest data that elucidates the role of the NLRP3 inflammasome in kidney diseases. RECENT FINDINGS: The NLRP3 inflammasome is not limited by traditional microbial stimuli of innate immunity and its connection with autophagy, apoptosis, fibrosis, and pro-inflammatory cytokines has broader implications for a variety of kidney diseases. In a wide spectrum of glomerular and tubulointerstitial diseases, the NLRP3 inflammasome is upregulated in both classical immune cells such as infiltrating macrophages and resident dendritic cells as well as in renal tubular epithelial cells, and even podocytes. Inhibition of the NLRP3 inflammasome ameliorates renal injury in a variety of animal models. Interestingly, this extends to models of proteinuria, which suggests that the deleterious effect of albuminuria on the proximal tubular epithelium and podocytes is, in part, mediated by inflammasome activation. SUMMARY: Recent studies in animal models, and still limited studies in humans, suggest a broad role for inflammasome activation in renal disease. Surprisingly, individual components of the inflammasome, independent of inflammasome activation, may also contribute to progressive renal injury. Additional, studies are needed to define the relative importance of the inflammasome in specific diseases and the therapeutic opportunities afforded by targeting the inflammasome.